Piercing the Structure of Tradition : Flute Performance, Continuity, and Freedom in the Music of Noh Drama - Anno, Mariko (Book collections on Project MUSE., 2020)
"Mariko Anno investigates flute performance as a site for exploring the relationship between tradition and innovation. This first English-language monograph traces the characteristics of the Noh flute (nohkan), its music, and transmission methods and considers the instrument's potential for development in the modern world. Anno examines the musical structure and nohkan melodic patterns of five traditional Noh plays and assesses the degree to which Issō School nohkan players maintain, to this day, the continuity of their musical traditions in three contemporary Noh plays influenced by William Butler Yeats"--